2003
DOI: 10.1364/ao.42.006016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nonintensified and intensified CCD detectors for laser-induced breakdown spectroscopy

Abstract: The performance and sensitivity of an intensified CCD array system and a nonintensified CCD array detector system are compared for laser-induced breakdown spectroscopy (LIBS). LIBS measurements were recorded in a calcium-based aerosol-seeded gas stream at ambient pressure. The signal-to-noise ratio based on the 393.37-nm calcium emission line was calculated as a function of detector delay with respect to the plasma-initiating laser pulse. Both ensemble-averaging and single-shot spectral analyses were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…As seen in Table 6, using this technique, LODs in the femtogram range can be achieved (Carranza et al 2001;Lithgow et al 2004) by employing very sensitive ICCD cameras (which have been shown to increase the S/N ratio by an order of magnitude; Carranza et al 2003), gated delay times, and high-energy lasers. However, FSA limits the size of particles that can be spectroscopically detected.…”
Section: Limits Of Detectionmentioning
confidence: 99%
“…As seen in Table 6, using this technique, LODs in the femtogram range can be achieved (Carranza et al 2001;Lithgow et al 2004) by employing very sensitive ICCD cameras (which have been shown to increase the S/N ratio by an order of magnitude; Carranza et al 2003), gated delay times, and high-energy lasers. However, FSA limits the size of particles that can be spectroscopically detected.…”
Section: Limits Of Detectionmentioning
confidence: 99%
“…138,145,158 The very fast gating capability is quite important since it allows a delay in starting detection in relation to application of the laser pulse, called delay time, removing from the detector signal the high intensity background continuum emission present in the early moments of plasma formation. In addition, it is used to optimize the detection for different decay rates between the plasma background continuum and the atomic emission for a given element.…”
Section: Detecting Systemsmentioning
confidence: 99%
“…84,120,128,164,165 Recent papers dealing with comparisons between detecting systems employing ICCD and a non-intensified CCD for LIBS reported better performances for the ICCD in terms of temporal resolution, dynamic range and detectivity, even with the intensifier gains adjusted to their minimum values. 138,158 Carranza et al 158 observed an increase in the signal to noise ratio (SNR) of the ICCD in relation to the CCD system from 2.8 to 25-fold for the 393.37 nm calcium emission line measured in calcium-based aerosols. Sabsabi et al 138 observed an increase in the LOD of the ICCD in relation to the CCD system from 1 to 2 orders of magnitude from analytical curves for Cu, Mn, Mg and Be in aluminum alloy samples and Ni, Fe and Ag in copper alloy samples.…”
Section: Detecting Systemsmentioning
confidence: 99%
“…A CCD detector provides less background signal, although ICCD improves the signal-tonoise ratio and is better for time-resolved detection using windows of a few nanoseconds [42]. Another problem related to ICCDs is the price, which is much higher than CCDs.…”
Section: Spectrometers and Detectorsmentioning
confidence: 99%